Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile - Pereira, Luis Alberto (Zootaxa, 2016)
Plateurytion roigi sp. nov. (Chilopoda: Geophilomorpha: Geophilidae) is fully described and illustrated from the holotype female from southern Chile (Region X (de Los Lagos region): Palena province). The new species seems particularly similar to P. gracilis (Gervais, 1849) (from Chile and Argentina), to which it is accordingly compared in detail for a confident identification. This is the sixth report of a species of the genus Plateurytion Attems, 1909, from Chile. The others are P. gracilis (Gervais, 1849); P. metopias (Attems, 1903); P. michaelseni (Attems, 1903); P. mundus (Chamberlin, 1955); and P. zapallar (Chamberlin, 1955). New geographic records are given for Plateurytion mauryi Pereira, 2008, which is reported for the first time from San Juan province, up to now only known from the type locality (in Mendoza province), central-western Argentina. Plateurytion yungarum (Pereira, 2005), is reported from the montane cloud forest altitudinal level of the Yungas forest of northwestern Argentina, until now it has only been recorded from the (lowest) montane forest altitudinal level of the Yungas.